2021
DOI: 10.1186/s12909-020-02414-9
|View full text |Cite
|
Sign up to set email alerts
|

What should medical students be taught about abortion? An evaluation of student attitudes towards their abortion teaching and their future involvement in abortion care

Abstract: Background One in three women in the United Kingdom (UK) will have an abortion before age 45, making abortion provision an essential aspect of reproductive healthcare. Despite this, abortion remains ethically contested and stigmatised, with variable teaching in UK medical schools and concerns about falling numbers of doctors willing to participate in abortion care. University College London Medical School (UCLMS) has designed practical, inclusive, teaching that aims to give students an understa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 10 publications
3
24
0
Order By: Relevance
“…As mentioned earlier, we intended to use region of domicile in the early years of life of the respondents as a proxy for religious belief. Since the southern part of Thailand is the main habitat for Muslim Thais, we expected that participants from Southern Thailand would show a more negative attitudes towards abortion in all conditions-in line with the report in much prior literature [31][32][33]. However, the results revealed no specific association pattern between regional domicile and abortion views.…”
Section: Results Discussionsupporting
confidence: 78%
“…As mentioned earlier, we intended to use region of domicile in the early years of life of the respondents as a proxy for religious belief. Since the southern part of Thailand is the main habitat for Muslim Thais, we expected that participants from Southern Thailand would show a more negative attitudes towards abortion in all conditions-in line with the report in much prior literature [31][32][33]. However, the results revealed no specific association pattern between regional domicile and abortion views.…”
Section: Results Discussionsupporting
confidence: 78%
“…Discussion: Our findings confirm the results of previous research indicating that medical students support the inclusion of abortion teaching in their curriculum, view abortion care as an essential part of reproductive healthcare and wish to have more training on it at undergraduate level. [5,6,[10][11][12] Previous research has also found that students' attitudes towards abortion differed according to religious and educational exposure, [6,13] and this diversity must be considered when delivering education. In line with this, our interviewees recognised the importance of teaching on conscientious objection and of facilitating communication between students holding differing views.…”
Section: Accommodating Diverse Viewsmentioning
confidence: 99%
“…(5) Furthermore, legal complexities and ethical concerns can make teaching abortion to medical students challenging. Research has found that the majority of UK medical students support the right to choose an abortion (are pro-choice) and support the inclusion of abortion teaching in their curriculum [5][6][7]. A survey of University College London medical students reported 83% of students identified as pro-choice, and that, regardless of their opinion on the right to choose, 96% of students rated abortion teaching as important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in China including almost 18000 students revealed that individuals who had the basic knowledge concerning sexual health became pregnant and underwent terminations less commonly (OR < 1, p < 0.05) [47]. Moreover, preparing medical students to be competent practitioners appears to contribute towards them viewing abortion as an essential aspect of women's healthcare [48]. A study carried out in Greece showed that despite the possibility of using contraception without prescription it was not frequently used.…”
Section: Sex Educationmentioning
confidence: 99%